A Case Report on Challenging Management of Multiple Neoplasms in Elderly - Ng Syiao Wei; Vanitha Palanisamy; Jothi Shanmuganathan; Urscilla Jaya Prahaspathiji; Hj Abd Razak Bin Hj Ahmad; Mahfida Mahat (Journal of Aging Research And Healthcare, 2020)
Multiple primary malignancies especially in the head and neck region is no longer a rare occurrence and the prevalence is increasing. They were described as synchronous when the malignancies present within 6 months of another or metachronous tumors if the subsequent malignancy presents 6 months later. Many etiologies had been hypothesised including similar carcinogens exposure, genetic susceptibility and mutation, immunodeficiency or treatment of the index tumor. Among the hypotheses, the most accepted theory was field cancerisation in which the occurrence of multiple primaries in the aerodigestive tract was due to persistent exposure of similar carcinogens through inhalation or oral intake . However the co-incidence of thyroid and aerodigestive malignancies is relatively low. Hereby we would like to report a case of a 74 years old lady with known esophageal squamous cell carcinoma presented with metachronous laryngeal squamous cell carcinoma and papillary micro carcinoma of thyroid.
Keywords: multiple neoplasms